2015
DOI: 10.1016/j.neuropharm.2015.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic diet prevents epileptogenesis and disease progression in adult mice and rats

Abstract: Epilepsy is a highly prevalent seizure disorder which tends to progress in severity and become refractory to treatment. Yet no therapy is proven to halt disease progression or to prevent the development of epilepsy. Because a high fat low carbohydrate ketogenic diet (KD) augments adenosine signaling in the brain and because adenosine not only suppresses seizures but also affects epileptogenesis, we hypothesized that a ketogenic diet might prevent epileptogenesis through similar mechanisms. Here, we tested this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
119
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 119 publications
(123 citation statements)
references
References 46 publications
3
119
0
Order By: Relevance
“…In epilepsy, chronic KD treatment can produce seizure control that extends well beyond cessation of the diet (e.g. [8385]) suggesting a persistent, possibly epigenetic, effect [32] – it remains to be seen if KD amelioration of ASD symptoms can persist in a similar manner. Finally, although ASD is more common in males, our positive results in females may provide additional hope for the 4 in 1000 females (650,000 individuals in the USA) who have ASD [86].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In epilepsy, chronic KD treatment can produce seizure control that extends well beyond cessation of the diet (e.g. [8385]) suggesting a persistent, possibly epigenetic, effect [32] – it remains to be seen if KD amelioration of ASD symptoms can persist in a similar manner. Finally, although ASD is more common in males, our positive results in females may provide additional hope for the 4 in 1000 females (650,000 individuals in the USA) who have ASD [86].…”
Section: Discussionmentioning
confidence: 99%
“…These outcomes suggest a long-lasting antiepileptogenic effect, possibly through epigenetic mechanisms [25]. The potential of KDs for antiepileptogenesis is supported by diverse animal research [2632]. …”
Section: Introductionmentioning
confidence: 99%
“…A subsequent study showed that a transient KD therapy restored normal adenosine levels and global DNA methylation levels in epileptic rats that were otherwise adenosine deficient and hypermethylated; importantly, transient KD therapy reduced seizure activity long-term, even after diet reversal to control diet [47 •• ]. Because KD therapy increases adenosine [47,48] and because adenosine blocks DNA methylation [49] it is likely that the KD exerts its disease modifying effects through an adenosine-dependent epigenetic mechanism.…”
Section: Disease Modifying and Epigenetic Mechanismsmentioning
confidence: 99%
“…The rats in KD-fed groups do not display a post-SE elevation of hippocampal pS6 levels that are observed in control animals after kainate induced SE [280]. Additionally, KD has also been shown to increase adenosine in the brain, and convey both acute anticonvulsant [281] and extended antiepileptogenic effects [282,283]. In a rat kainate-SE model, KD animals experienced fewer and less intense SRS, and reduced mossy fiber sprouting in the supragranular layer of the DG compared to control groups.…”
Section: Ketogenic Diet Inhibition Of Epileptogenesismentioning
confidence: 99%
“…However, no difference in pyramidal cell loss was observed between treatment and control groups [284]. KD treatment has been shown to not only inhibit or delay kindling epileptogenesis in rats and mice, but also to prevent the progression of the disease after pilocarpine induced SE in rats [283]. Furthermore, KD treatment improves deficits in spatial memory function in kindled rats [285].…”
Section: Ketogenic Diet Inhibition Of Epileptogenesismentioning
confidence: 99%